Navigating Travel Writing and Digital Humanities: the “Anglophone Travellers in Portugal” Project and its Visual Narratives - Maria Beatriz Rodrigues; Maria Zulmira Castanheira (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
ABSTRACT: This article aims to present the “Anglophone Travellers in Portugal” project carried out at CETAPS, focusing on its visual dimension. After decades of analysing the works using close reading methods, we have adopted Digital Humanities approaches to deal with the large amount of data generated. With these notions in mind, we have taken on data visualization tools as a way of analysing, interpreting and communicating our findings related to the travel narratives we have gathered in our database, written by Anglophone authors who travelled in Portugal. These travellers show us a different perspective on Portuguese culture, history and geography and, in order to draw meaning from their narratives, we have to look at them in an interdisciplinary way. This will be possible through the advancement of the project’s visual identity, both by developing the visuals of the associated repository and website and by the inclusion of digitised images of the illustrations present in the works incorporated in our database. Therefore, in this article, we will start by demonstrating the importance of illustrations and images in literary works; we will then delimit the illustrations that can be found in the “Anglophone Travellers in Portugal” project, and we will finish by describing the process of scanning, categorizing and organizing the generated images. This account will allow us not only to share our findings with the public but also to pave the way for new stories, discoveries and participations.